2014
DOI: 10.1128/jvi.01714-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasmacytoid Dendritic Cells Sense Lymphocytic Choriomeningitis Virus-Infected Cells In Vitro

Abstract: bWe previously reported that exosomal transfer of hepatitis C virus (HCV) positive-strand RNA from human Huh-7 hepatoma cells to human plasmacytoid dendritic cells (pDCs) triggers pDC alpha/beta interferon (IFN-␣/␤) production in a Toll-like receptor 7 (TLR7)-dependent, virus-independent manner. Here we show that human pDCs are also activated by a TLR7-dependent, virus-independent, exosomal RNA transfer mechanism by human and mouse hepatoma and nonhepatoma cells that replicate the negative-strand lymphocytic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Recent studies showed that pDC sense hepatitis C virus (HCV)-or lymphocytic choriomeningitis virus (LCMV)-infected cells (59,60), and viral transmission by cell-to-cell contacts are more potent inducers of IFN than infection by cell-free viral particles (61,62). We confirmed and extended these data to HIV-1 transfer from primary pDC to CD4 T lymphocytes.…”
supporting
confidence: 77%
“…Recent studies showed that pDC sense hepatitis C virus (HCV)-or lymphocytic choriomeningitis virus (LCMV)-infected cells (59,60), and viral transmission by cell-to-cell contacts are more potent inducers of IFN than infection by cell-free viral particles (61,62). We confirmed and extended these data to HIV-1 transfer from primary pDC to CD4 T lymphocytes.…”
supporting
confidence: 77%
“…HCV-infected cells produce these vesicles via the cellular exosomal pathway and without the requirement of viral structural proteins (12). This process is presumably similar for LCMV (13). While HAV was originally classified as a nonenveloped virus, recent work demonstrated that viral capsids containing HAV genomes can acquire cell membranes via the exosomal pathway and are thus identified as an enveloped form of HAV (eHAV) (14).…”
Section: Pdc Activation By Cell-cell Contact With Virus-infected Cellsmentioning
confidence: 99%
“…Nonetheless, on the downside, this vesicular form of HAV is also an efficient PAMP carrier for the activation of the pDC response (11). For these various viruses, the exosomal transfer of the immunostimulatory RNA to pDC commonly requires cellcell contact with infected cells (11)(12)(13). Importantly, we recently illustrated that the cell-cell sensing of infected cells by pDC might involve other types of PAMP carriers.…”
Section: Pdc Activation By Cell-cell Contact With Virus-infected Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the K465V and G467K mutations may interfere with virus cell entry, despite these mutations being located within the CD of GP2. Interestingly, human pDCs are refractory to rCl-13 WT infection when infected ex vivo (62), suggesting the existence of a yet-unidentified cell entry pathway required for infection of pDCs in vivo that could be affected by K465V and G467K mutations. Published data support a very strong correlation between high affinity for ␣DG of the LCMV GP and the virus's ability to persist.…”
Section: Discussionmentioning
confidence: 99%